Crimes on the edge? Criminal activities and the crime-terror nexus in the Kenyan peripheries of the Indian Ocean - Badurdeen, Fathima Azmiya (Global crime, 2023)
Maritime security threats in the East African coastal peripheries are greatly interwoven with local crimes, economies, and socio-political lifestyles. How crimes are viewed, defined, and categorised as legal and illegal by the locals elucidates how the crime-terrorism nexus is contextualised in specific localities along the coastal seafronts. Often, financial-motivated crimes have the potential to go hand in hand with ideologically driven terrorist activities, where both syndicates operate discreetly in these communities. Based on an ethnographic study in Kenya, this article interrogates the local meanings and understandings of criminal activities in peripheral societies to determine how local crimes intersect with terrorism-related activities. The crisscrossing modus operandi of criminal syndicates and terrorist networks provides each other with safe havens, secrecy in operations, and a vulnerable base of supporters in environments where state-citizen relationships are deteriorating.